Genetic characterization of popcorn (Zea mays everta) genotyping based on SSR (simple sequence repeats) markers. Issue 1 (April 2020) - Isnaini, Muzdalifah; Sunarti, Sri; Andayani, N.N.; Pabendon, Marcia B.
Abstract: Popcorn variety is modified corn that makes good form, crunchy texture, and high yield. Through this research, expected pre-eminent maize national variety can replace role of import maize variety which used in making of popcorn so that the intention of self sufficiency in food and improvement of domestic resource quality can be reached. This research aimed to determine relation of genetic and genetic diversity of popcorn using SSR. The study was conducted at the Molecular Biology Laboratory, Cereals Crop Research Institute. The number of genetic collected popcorn lines consisted of 30 genotypes and tested by 18 markers of SSR. The result show polymorphism value was 0.30 with average value 2 allele/locus and the allele size locus of allele between 106.0-427.0 bp, size measure of minimum allele of umc 1545 while size measure of allele highest of Phi 093. Correlation value of cophenetic (r) equal to 0, 82 pertained is good enough (good fit) to looking like matrix of genetic, showing accuracy of subdividing of germplasm into cluster still is good enough. The genetic diversity of popcorn analyzed show genetic viability of popcorn analyzed form 4 cluster and there are 11 tide opportunity of cross. This matter indicated that maize lines of popcorn this have earned to be exploited in making of hybrid maize.